Alexander of Aphrodisias and the problem of instrumentality’ of logic. Notes on in A. Pr. 2, 22-33 - Salles, Ricardo (Estudios de Filosofía, 2009)
Ricardo Salles’ contribution is focused on Alexander’s Peripatetic interpretation against the Stoic thesis that logic is not an “instrument”, but a “part” of philosophy. According to Alexander, if logic were part of philosophy, as the Stoics maintain, philosophy could not occupy the highest place in the hierarchy of knowledge. Salles takes this to be paradoxical since both the Stoics and the Peripatetics consider that philosophy is, due to its object, the highest discipline. According to Salles, Alexander’s acute criticism is not penetrating enough to make obvious a real inconsistency in Stoicism. In his view, Alexander’s main weakness is that the reasoning on which such criticism is based depends upon some Aristotelian assumptions that the Stoics reject.